Using primary care data to assess population-level estimates of maternal smoking and nicotine replacement therapy during pregnancy - Dhalwani, Nafeesa N. (2014)
Background: Smoking in pregnancy is the most significant preventable cause of poor health outcomes for women and their babies and, therefore, is a major public health concern. In the UK there is a wide range of interventions and support for pregnant women who want to quit. One of these is nicotine replacement therapy (NRT) which has been widely available for retail purchase and prescribing to pregnant women since 2005. However, measures of NRT prescribing in pregnant women are scarce. These measures are vital to assess its usefulness in smoking cessation during pregnancy at a population level. Furthermore, evidence of NRT safety in pregnancy for the mother and child’s health so far is nebulous, with existing studies being small or using retrospectively reported exposures.